Bioinformatics analysis and experimental validation of ferroptosis in peri-implantitis - ZHANG Zhewei, WANG Jiaohong, WU Wei, DONG Shuo, LI Guoqing, TANG Chunbo (Editorial Office of Stomatology, 2024)
Objective To investigate the key genes associated with ferroptosis in peri-implantitis and explore the potential mechanisms regulating peri-implantitis. Methods Several datasets were obtained from the GEO database. Differential expressed genes were screened, and GO and KEGG analyses were performed. A PPI network was constructed using the STRING website. Key genes were validated using a test set, and the diagnostic value of key genes was determined. The content and proportion of 22 immune cells in peri-implantitis tissues were obtained through immune infiltration analysis. Key genes were validated by qRT-PCR and Western Blot(WB). Results There were 1 138 differential genes between peri-implantitis tissues and normal gingival tissues, of which 29 were related to ferroptosis. The gene expression in peri-implantitis tissues mainly involved processes such as immune response activation. Five key genes in the ferroptosis-related differential genes, namely SOX2, GJA1, IL1B, GPX2 and CHAC1, were differentially expressed in peri-implantitis tissues and had high diagnostic value. Immune infiltration analysis showed significant changes in immune cells such as memory B cells and plasma cells in peri-implantitis tissues. qRT-PCR and WB confirmed significant differential expression of mRNA and the protein transcribed by key genes. Conclusion Differential genes between peri-implantitis and ferroptosis are screened using bioinformatics analysis and biological validation, providing new insights into the study on peri-implantitis.